Analysis of Student Learning Interest in Arabic Language Subjects at Mts Manba'ul Huda Sekaran-Balen - Munawaroh, Bashirotul; Khoirul Faizin (Assuthur: Jurnal Pendidikan Bahasa Arab, 2025)
The interest in learning is an option in carrying out an activity and could arouse a person's desire to make a willingness to learn. This interest is very important. It will affect the understanding of the received material and the learning outcomes that will be obtained. This study aimed to determine the level of students’ interest in learning at MTs Manba’ul Huda Sekaran. Quantitative descriptive method was used as research design. The characteristics of this quantitative descriptive research were in the form of numerical data. Conclusions were drawn based on the words and numerical data. Meanwhile,exposure of descriptive statistical data was shown in the form of tables and images obtained from observations, questionnaires, documentation, and interview with the Arabic teachers at MTs Manba’ul Huda Sekaran. The data described was then discussed and analyzed.